A Hydrogen‐Bonded Hexagonal Buckybowl Framework. Issue 48 (26th October 2017) - Hisaki, Ichiro; Toda, Hideaki; Sato, Hiroyasu; Tohnai, Norimitsu; Sakurai, Hidehiro
Abstract: A hydrogen‐bonded two‐dimensionally networked buckybowl architecture is presented. Two types of hexagonal network (HexNet) structures (CPSM‐1 andCPSM‐2 ) have been achieved based on a sumanene derivative (CPSM ) possessing 4, 4′‐dicarboxy‐ o ‐terphenyl groups in the periphery.CPSM‐1 has a waved HexNet structure with an alternate alignment of upward and downward bowls.CPSM‐2 has a bilayered HexNet structure composed of hamburger‐shaped dimers of the bowls. This demonstrates that non‐planar π‐systems can be networked two‐dimensionally by an appropriate supramolecular synthon to achieve structurally well‐defined unique bumpy π‐sheets. Furthermore, we revealed thatCPSM‐2 undergoes anisotropic shrinking along the c axis by 11 % under high pressure conditions (970 MPa). The shrinkage is brought about by offset sliding between bumpy π‐surfaces of the bilayered HexNet sheets. Abstract : A sumanene derivative with 4, 4′‐dicarboxy‐ o ‐terphenyl groups in the periphery forms two kinds of hydrogen‐bonded, hexagonally networked, layered architectures with curved and bumpy surfaces. One of them showed anisotropic shrinkage of the crystallographic cell parameters under high‐pressure conditions.